Synthesis and Characterization of New Hydrogels Through Copolymerization of N-acryloyl-tris-(hydroxymethyl)aminomethane and Different Crosslinking Agents - Cuggino, Julio César (2008)
In this study, new hydrogels in rod shape were prepared from N-acryloyl-tris-(hydroxymethyl) aminomethane (NAT) using three different crosslinking agents: poly(2-methyl-2-oxazoline) bismacromonomer (BM), ethylene glycol dimethacrylate (EGDMA) and N,N´-methylenebisacrylamide (BIS). Dimethylformamide (DMF) was used as solvent and 2,2´-azobisisobutyronitrile (AIBN) as initiator. Polymeric matrices with different properties were obtained by free radical polymerization by changing the crosslinker (BM, EGDMA or BIS) or the concentration of BM. The hydrogel structures were characterized by high resolution magic angle spinning (HRMAS) NMR technique. Swelling experiments and rheological studies were used to test the water absorption capacity and viscoelastic properties of the hydrogels, respectively. For a given NAT/crosslinking agent molar ratio, the hydrogel synthesized with BM displays higher water absorptive capacity and larger range of linear viscoelasticity than those synthesized with BIS or EGDMA. The relatively larger hydrophilic character of the former and the lower crosslinking density generated by the longer molecules of BM might be the cause of this behavior. The results also reveal that water diffuses into the network following a non-Fickian mechanism. This is concluded from the value of the diffusion exponent n, which is higher than 0.50. The elastic modulus and the equilibrium water content (EWC) measurements suggest that these materials may have potential application as biomaterials.